Exploring the Drivers Behind Parents' Intentions to Support Fine Art Education for Primary and Middle School Students: A Case Study in Chengdu, China - Wei, Qin (Scholar: Human Sciences, 2026)
Purpose: The study investigated the effect of seven independent variables (perceived ease of use, perceived usefulness, social influence, hedonic motivation, self-efficacy, perceived satisfaction, subjective norms) on the dependent variable (behavioral intent). Furthermore, it is designed to identify significant differences between variables. Research design, data, and methodology: The project-objective consistency index was used to evaluate the validity of this study. Cronbach's Alpha was used for the pilot test (n=30) to evaluate reliability. Multiple linear regression analysis was performed on 100 valid questionnaires of students from the Western District of Chengdu Baotongshu Primary School, Chengdu Shishi Joint Middle School, and Chengdu Baotongshu Middle School to verify the significant relationship between the variables. Subsequently, 40 students underwent a 14-week Intervention Design Implementation Then, the quantitative results before and after idioms were compared using a paired sample T-test. Results: The analysis revealed that perceived ease of use, hedonic motivation, and subjective norm significantly influence parents' behavioral intention to support art learning. The comparison results of the paired sample T-test further confirmed these findings, showing significant differences in perceived ease of use, hedonic motivation, subjective norms, and behavioral intent between the pre-IDI and post-IDI stages. Conclusion: These findings can be used to develop strategies encouraging parental involvement in students' fine art learning, enhancing the overall learning experience.